The effect of the Cornwall and Isles of Scilly helicopter ambulance unit on the ambulance services' ability to deliver acutely traumatized patients to hospital. Issue 2 (June 1992) - Rouse, A
Abstract : Objective: to determine whether the use of a helicopter ambulance unit enabled an ambulance service to deliver acutely traumatized patients to hospital more quickly. Design: retrospectively collected ambulance service and hospital records data analysed longitudinally. Settings: The ambulance service and the major casualty department in Cornwall. Intervention: the provision of a helicopter ambulance unit to a county ambulance service. Subjects: patients with compound lower limb fractures carried as emergencies by an ambulance service. Principle outcome measure: ambulance 'mission times'. Results: the ambulance services' ability to deliver emergency patients to hospital more quickly when the helicopter unit was available was not demonstrated. In some instances availability of the helicopter unit probably delayed the timely delivery of emergency patients to the casualty department. Conclusion: until a more effective helicopter deployment strategy is in operation it is unlikely that mission time savings will occur.